A biomechanical comparison between the single-axis and multi-axis total knee arthroplasty systems for the stand-to-sit movement - H. Wang (2018)
Background. Compared to the design of a traditional multi-axis total knee arthroplasty, the single-axis arthroplasty studied has a fixed flexion/extension center of rotation in the femoral component. The influence of this characteristic on functional daily activity, i.e., stand-to-sit, is not well understood. The purpose of this study was to investigate the effect of different arthroplasty designs on knee kinematic and lower limb muscular activation for the stand-to-sit movement. Methods. Sixteen unilateral, posterior-stabilized knee arthroplasty participants (8 single-axis and 8 multi-axis) with excellent Knee Society scores performed 4 trials of the stand-to-sit test. Three-dimensional video analysis of whole body and joint kinematics and electromyography analysis of quadriceps and hamstrings were conducted. One-way ANOVAs were used for statistical analyses (α = 0.05). Findings. The multi-axis group showed some functional adaptations while sitting down. The single-axis group exhibited less arthroplasty limb quadriceps electromyography and hamstring co-activation electromyography than the multi-axis group. For the arthroplasty limb, single-axis demonstrated less abduction angular displacement and reached peak abduction earlier than the multi-axis arthroplasty limb. The estimated effect size for this study was 0.196. Interpretation. The single-axis design requires less eccentric knee extensor muscle activation and exhibits greater medio-lateral stability than the multi-axis designs. Findings from this study could provide useful information to orthopedic knee surgeons and rehabilitative specialists. © 2004 Elsevier Ltd. All rights reserved.